Robust Position Tracking Control of an Electro-Hydraulic Actuator in the Presence of Friction and Internal Leakage - Has, Zulfatman; Rahmat, Mohd Fua’ad; Husain, Abdul Rashid; Ishaque, Kashif; Ghazali, Rozaimi; Ahmad, Mohamed Noh; Md Sam, Yahaya; Md Rozali, Sahazati (Springer, 2013)
This paper proposes an improved robust position controller for the electro-hydraulic actuator system using the varying boundary layered sliding mode control scheme. The proposed scheme has the ability to improve the position tracking performance of the actuator in the presence of friction and internal leakage. The former is represented using the LuGre model while later is modelled as a turbulent flow. To evaluate the effectiveness of the proposed method, MATLAB simulations are carried out under friction and leakage effects. Its performance is compared with the conventional PID and fuzzy PID (FPID) methods. Finally, an experimental rig that comprises of a single-rod and double acting hydraulic cylinder is set up to validate the proposed idea. The software development is carried out in the DSpace 1104 environment using a TMS320F240 digital signal processor. The superiority of the proposed method over the PID and FPID in terms of tracking position is highlighted by simulation and experimental results